Some Structural Features of Sulu Terrane (Eastern China) from Well Logs and Images - AMA Salim, HP Pan, . (2008)
he structure of Sulu Ultrahigh-Pressure (UHP) metamorphic belt in eastern China is so complicated and different models have been suggested by many authors. Although the interpretation of different structural features from geophysical logs is quite ambiguous, but availability of various well logs and images made it possible. At least 2 sets of faults are identified within the studied depth range.